The Law Application of Land Procurement for Development in Public Interest - Hendri Cahyono; Gunarto Gunarto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Implementation of the application of Article 35 of Act No. 2 of 2012 concerning Land Acquisition for the Development of Toll Roads in the Public Interest. The value of compensation based on the results of the Appraiser's assessment becomes the basis for deliberation to determine compensation. In Article 35 of Act No. 2 of 2012 it is stated that if in the case of certain land parcels that are affected by land acquisition there are remnants that can no longer be functioned according to their designation and use, the entitled Party may request a complete replacement of the parcel of land. What is meant by